Recent Water Quality Assessment Of Buriganga and Turag River (Chemical Engineering Research Bulletin, 2023)
The Buriganga and Turag rivers are two of the most vital rivers in Bangladesh. Over the past 10-15 years, both rivers have suffered significantly from wastewater pollution. The main threat to their water quality is the discharge of untreated wastes due to their proximity to densely populated areas. Inadequate wastewater management is the key factor behind this pollution. Monitoring various physicochemical parameters such as pH, TDS, TSS, EC, BOD, COD, and alkalinity is essential to assess water quality. This study aims to evaluate the water quality of these rivers by analyzing key parameters and comparing them with standard values. Equipment-based methods were used to determine parameters like pH, TDS, TSS, and EC, while others were measured manually. The TDS levels range from 482 mg/L to 330 mg/L for the Turag River and 381 mg/L to 259 mg/L for the Buriganga River. The BOD values are between 112 and 165 mg/L for the Turag River, and 75 to 174 mg/L for the Buriganga River, indicating unsuitability for aquatic life. Although electrical conductivity remains within acceptable limits, water alkalinity shows significant deviations from standard values.Chemical Engineering Research Bulletin 23(2023): 30-35